Plastome sequences of an ancient fern lineage reveal remarkable changes in gene content and architecture. Issue 7 (28th July 2017) - Labiak, Paulo H.; Karol, Kenneth G.
Abstract : PREMISE OF THE STUDY: Comparative analyses of plastid genomes have suggested that gene order and content are relatively stable across the main groups of land plants, with significant changes rarely reported. We examine plastome organization and RNA editing in ferns and report changes that add valuable information on plastome evolution in land plants. METHODS: Using next‐generation sequencing methods, we fully sequenced plastomes from three species of Schizaeaceae, and compared their plastomes with other groups of land plants to study changes in gene composition, plastome architecture, and putative RNA editing sites. We also performed maximum likelihood and Bayesian inference phylogenetic analyses using 46 plastid‐encoded genes, including 26 ferns, two gymnosperms, and five angiosperms. KEY RESULTS: Within Schizaeaceae, plastomes were similar to each other in gene content and architecture. Striking changes compared with other ferns include the complete loss of ndh genes and reduction of the small single copy. Putative RNA editing was identified in all three plastomes, a characteristic that is shared with other fern groups. The monophyly of Schizaeales and Schizaeaceae was confirmed. CONCLUSIONS: The plastomes of Schizaea are the smallest reported for a fern so far. The loss of the ndh gene suite is associated with the reduction of the small single copy, instead of the inverted repeat as noted for other groups of plants. Putative C‐to‐U and U‐to‐C transitions were observed in several instances in the three plastomes, suggesting that posttranscriptional modification of RNA is likely a common phenomenon in this clade as well.